A Vila e a Prisão: novas perspectivas do conceito de prisionização - Rossler Junior, Eduardo Henrique (2019)
This work is situated within the sociology of prisons field. More specifically, in the process of apprehending and updating studies on the effects of the prison system on certain groups of society, prison. The object of interest is the so-called "vila", a group of houses destined to the managers of the Campinas-Hortolândia penitentiary complex, in the interior of the State of São Paulo. Located less than 60 meters from the prison walls, this work intends to observe and analyze micro-relations between residents and former residents of this locality and how prison contributes to the organization of their daily lives. In keeping with the changes in the public policies of the prison system in São Paulo, such as the expansion of prisons, its control by the criminal factions and the war on drugs, this work sought to understand how these issues were managed by this group in the search for strategies of maintaining the normality of social relations established in this place. Through interviews and the reconstruction of the collective memory of the group, it was possible to perceive that the influence of the prison generates not only a change in the discourse about the insecurity in the conscious plane, but also a deep process of subjectivation of the prison logic, reorganizing the strategies for guarantee cohesion and solidarity of the group. Through a symbiotic (between prison and village) and conflicting process, the relationships observed were shown as a constant effort by families to reinforce and re- signify the elements family and community institution, through adaptations that react to daily prison. These adaptations are incorporated into the everyday and normalized, becoming no longer objects of disruption of order, but rather elements that are part of the constitution of the community itself. Neither inside nor outside, but through prison, the village makes possible a sui generis community, an exacerbation of the influence of the prison in the groups in which it transforms. In it, the distinctions between public and private are weakened, as the solidarity between members strengthens. This causes, as I have tried to demonstrate, a community with a high degree of interdependence, which results in an odd, detached behavior of the broader society. It was also possible to observe the dilemmas and the great difficulty of the adaptation of these families to social contact, especially at the moment when they disengaged from their positions and closed the connections with the village community.